Translational albumin nanocarrier caging photosensitizer for efficient cancer photodynamic therapy - Luo, Jie; Miao, Zhijun; Huang, Xinglong; Yang, Yifan; Liu, Ming; Shen, Gang; Yang, Tao (Frontiers in Bioengineering and Biotechnology, 2023)
It still remains a great challenge to efficiently treat malignant cancers which severely threaten human health. Photodynamic therapy (PDT) as a localized therapeutic modality has improved the therapeutic efficacy via chemical damage through reactive oxygen species (ROS). However, their efficacy is severely hampered by insufficient targeted delivery of photosensitizers owing to the lack of suitable carrier with facile preparation process and the clinical applicability. Herein, we applied clinically approved human serum albumin as the nanoreactor to encapsulate photosensitizers Chlorin e6 (Ce6) for enhancing their tumor accumulation and subsequently potent PDT effect against bladder cancer models. Albumin-loaded Chlorin e6 nanoparticles (CA-NPs) with rational nanoscale size exhibit increased ROS production and excellent resistance to photobleaching. Moreover, CA-NPs could be efficiently internalized by tumor cells and locate in the lysosome, while they rapidly translocate to cytosol after irradiation to induce remarkable cytotoxicity (IC50 ~5.8 μg/mL). Furthermore, CA-NPs accumulate effectively in tumor tissue to afford total eradication of murine bladder tumor after single injection. More importantly, we also evidence the superior PDT effect in fresh human bladder tumor tissues via abundant ROS generation and subsequent cell apoptosis. These findings demonstrate that human serum albumin acts as a universal tool to load small organic photoactivatable molecule with remarkable effectiveness and readiness for clinical translation.